2020
DOI: 10.1108/jrim-10-2019-0171
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the optimized social advertising strategy that can generate consumer engagement with green messages on social media

Abstract: Purpose Given that many consumers are skeptical about environmentally based advertising campaigns, the purpose of this study is to propose an optimized message strategy to facilitate consumer engagement with green messages in social media contexts. Design/methodology/approach Four empirical studies are conducted using self-report questionnaires to test proposed hypotheses with a focus on the interplay between claim specificity and benefit appeals in green advertising on social media. Findings The current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 69 publications
(93 reference statements)
1
28
0
Order By: Relevance
“…Celebrity endorsement refers to the strategy of promoting products, services and ideas based on the social influence of well-known individuals (Kyu Kim et al , 2021). A celebrity status is often deemed for someone who is talented in certain fields (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Celebrity endorsement refers to the strategy of promoting products, services and ideas based on the social influence of well-known individuals (Kyu Kim et al , 2021). A celebrity status is often deemed for someone who is talented in certain fields (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Verma and Yadav (2021) reviewed the literature on eWOM from 2000 to 2020, discovering that hospitality and tourism is one of three clusters as important subthemes of eWOM research. However, eWOM messages may have different effects on people depending on contexts and settings (Sussman and Siegal, 2003; Kyu Kim et al , 2020). Wolny and Mueller (2013) analyzed the participation of fashion consumers in eWOM communication on social media, extending the eWOM framework to other contexts, and indicated that they would like to see more extensive eWOM research conducted in the fashion context, which paved the way for future studies.…”
Section: Theoretical Perspectives and Model Developmentmentioning
confidence: 99%
“… Yang et al (2015) find that, when green advertising emphasizes more on altruism, compared with specific advertising claims, abstract advertising claims can intensively improve green consumers’ willingness to purchase. Kim et al (2021) explore optimized social advertising strategies that can generate consumer engagement with green messages on social media. They investigate the effect of claims’ specification and interest appeal on consumers’ degree of involvement on social platforms and show that consumers’ degree of self-structural moderates the interaction effect of claim specificity and benefit appeals type on consumers’ degree of involvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing research on green advertising has mainly focused on the effect of environmental involvement, self-construction and directional control on green newsfeed advertising, respectively ( Chang et al, 2015 ; Yang et al, 2015 ; Kim et al, 2021 ). However, it is still necessary to investigate the effect of green newsfeed advertising on consumers’ psychology and behavior through empirical methods.…”
Section: Literature Reviewmentioning
confidence: 99%